Solamargine Alleviated UVB-Induced Inflammation and Melanogenesis in Human Keratinocytes and Melanocytes via the p38 MAPK Signaling Pathway, a Promising Agent for Post-inflammatory Hyperpigmentation - Zhao, Juemin; Dan, Yanjun; Liu, Ziqi; Wang, Qianqian; Jiang, Min; Zhang, Chengfeng; Sheu, Hamm-Ming; Lin, Chrang-Shi; Xiang, Leihong (Frontiers in Medicine, 2022)
Post-inflammatory hyperpigmentation (PIH) is a common acquired pigmentary disorder occurring after skin inflammation or injury. Ultraviolet B irradiation could exaggerate PIH clinically due to its effect on promoting cutaneous inflammation and melanogenesis in keratinocytes and melanocytes, respectively. Solamargine (SM), a steroidal alkaloid glycoside extracted from Solanum undatum, significantly inhibits Ultraviolet B (UVB)-induced pro-inflammatory cytokines IL-1α, IL-1β, IL-8, and IFN-γ, as well as paracrine melanogenic factors ET-1, α-MSH, and bFGF in human keratinocytes. Additionally, SM significantly attenuated UVB-induced melanin synthesis in human epidermal melanocytes through down-regulation of tyrosinase activity and expression of MITF, TRP-1, TRP-2, and tyrosinase. SM exerted an anti-inflammatory effect in UVB-irradiated keratinocytes through the p38 MAPK/Nrf2/HO-1 signaling pathway. With its anti-inflammatory and whitening effect, SM may improve PIH through paracrine regulations of keratinocytes and direct action on melanocytes, making it a promising agent for PIH.